Indoor Microbial Contamination Through Water Mist Aerosol at Public Restaurants - Maryam, Zahaba; Rafiqa Azira, M. R.; Noor Faizul, Hadry; N. Norhidayah, A.; Mohd Shukri, M. A. (Penerbit Universiti Teknologi Malaysia, 2015)
In Malaysia and many other Asian countries, countless number of restaurants are made of open or semi-open air buildings. These restaurants are commonly located beside roads, factories, and construction sites. The foods are often exposed to the air, increasing their tendency to be contaminated due to poor indoor and outdoor air quality. There are very few studies characterising and comparing the levels of indoor air pollutants in restaurants. Other than that, scarce data are available on dining establishments especially in the presence and absence of water mist application system. Due to these reasons, no best practices or guidelines can be developed. Hence, this present study aimed (1) to assess and compare the physical indoor air quality (IAQ) characteristics and airborne pollutants between different types of restaurant settings; (2) to identify microbes isolated in the presence and absence of water mist system; (3) to analyse bacterial counting within and between the different restaurant settings; and (4) to determine the relationship between physical IAQ characteristics and airborne microbial contaminants. Instruments known as Dustmate and VelociCalc® Multi-Function Ventilation Meter 9565 were used to measure the physical IAQ characteristics and airborne particulate matters. On the other hand, Surface Air System Indoor Air Quality (SAS IAQ) was use to seize the microbial contaminants. All the data obtained were compared with the standard reference known as the Industrial Code of Practice on Indoor Air Quality (2010) constructed by the Department of Occupational Safety and Health (DOSH). This study later indicated that the level of indoor PM10 concentrations was influenced by changes of physical IAQ parameters at the two restaurants investigated. As the PM10 increased, the colony forming unit (CFU) counting also increased. Although microbial contaminations were found during both periods of exposure (i.e., in the presence and absence of water mist) at both restaurants, significant relationship between the parameters measured cannot be determined. The bacterial species obtained during the presence and absence of water mist application system for both of the restaurants were also identified. Gemella morbillorum was found as the most dominant species, followed by other species such as Aerococcus viridans, Globicatella sanguinis, Leuconostoc spp., and Proteus penneri.